A Proposal of Conducting Bioequivalence Trials with Gastric pH Modulators for Two Oral Formulations Demonstrating Different Dissolution Profiles at Elevated pH. Issue 6 (16th August 2019) - Zhu, Hao; Chen, Xiaomei; Ahmed, Mariam; Wang, Yaning; Liu, Qi; Uppoor, Ramana S.; Kuemmel, Colleen; Mehta, Mehul
Abstract : In this paper, a special case for bioequivalence evaluation of oral formulations is discussed. Drug formulations with different forms of active moieties (e.g., free base and salt) may yield different dissolution characteristics and, thus, differ in absorption at elevated gastric pH. However, routine bioequivalence trials using subjects with normal gastric pH (i.e., 1) may fail to identify these differences because dissolution/absorption profiles of the two formulations at normal gastric pH are similar. In the case of palbociclib, it is confirmedthat the free base and salt formulations showed different absorption in patients with different gastric pH. Significant reduction in drug absorption was observed only in patients with elevated gastric pH using free base formulation. The discovery that the free base had significantly reduced absorption hinged on the inclusion of enough patients with elevated gastric pH to detect a difference in a bioequivalence trial. This raises a concern, as demonstrated through simulation, that dissolution/absorption differences in other formulations could be missed in routine bioequivalence trials. Aside from differences in active pharmaceutical ingredients (APIs), other factors, such as changes in excipients or manufacturing methods, may also lead to exposure differences between formulations at elevated gastric pH. For formulations containing different forms of the same active moiety or the same API and showing different dissolution profiles at elevated pH (i.e., pH 4–6.8), evaluation of bioequivalence with gastric pH modulators (e.g., a H2 blocker) in addition to routine bioequivalence assessments may help to ensure therapeutic equivalence in patients with elevated gastric pH.